Russian Tax System: System Deficiencies and the Direction of the Improvement - SHVETSOV, Yury G.; BALIKOEV, Vladimir Z. (Journal of Advanced Research in Law and Economics; Vol 8 No 4(26) (2017): JARLE Volume 8 Issue 4(26) Summer 2017, 2017)
The article considers questions about a crisis status of the taxation system in Russia and prospects of its overcoming. The major defects of the current tax system have been revealed and analyzed; its exclusively fiscal orientation in economy has been proved. Strategy of realization of the tax reform is reasonable; the characteristic has been given to its major components, one of which is introduction of different vector of taxes.